Comparison of Efficacy of Oral Tofacitinib (JAK Inhibitor) Combined with Narrow Band UVB Vs Alone Oral Tofacitinib in Patient with Vitiligo at Tertiary Care Hospital, Karachi - Iqra, Soonha; Ghafoor, Rabia; Abro, Muhammad Tarish; Qadir, Misbah Zari; Muhammad Khurram,; Ali, Asif (Indus Journal of Bioscience Research, 2024)
Objective: compare the oral Tofacitinib added to NB-UVB phototherapy versus Tofacitinib monotherapy in patients with vitiligo, at a tertiary care teaching hospital in Karachi. Methods: After the ethical approval from the institutional review board, this open-label, non-randomized study is conducted at the Department of Dermatology, JPMC, Karachi from April 2024 to Sep 2024. Through non-probability consecutive sampling, 40 patients aged 18 above, both genders, diagnosed of vitiligo with stable lesions for half a year were included in the present study. The patients were divided into groups: Group B patients that received only oral Tofacitinib 5 mg twice a day (n=20) and Group A patients treated with oral Tofacitinib 5 mg twice a day in combination with NB-UVB phototherapy three time weekly (n=20). Results: At 12 weeks, the VASI score showed significant improvement in the Tofacitinib + NB-UVB group (36.8 ± 8.3) compared to the Tofacitinib alone group (54.15 ± 9.5, p < 0.0001). The percentage improvement in VASI was also significantly higher in the combination therapy group at 57.4 ± 9.7% versus 36.7 ± 9.9% in the monotherapy group (p < 0.0001). Furthermore, the efficacy outcome, defined as ≥51% improvement in re-pigmentation, was achieved in 15 patients (75%) in the Tofacitinib + NB-UVB group compared to only 1 patient (5%) in the Tofacitinib alone group, with a highly significant p-value of <0.0001. Conclusion: Oral tofacitinib complemented with NB-UVB phototherapy is more effective than Tofacitinib monotherapy in re-pigmentation in vitiligo patients.